The Role and Impact of Freelancing in Preventing Youth Migration (Salam International Academic Journal, 2025)
This study evaluates the role and impact of freelancing in preventing youth migration. It investigates how freelancing can reduce or mitigate youth migration, particularly in regions with limited employment opportunities where unemployment forces young people to migrate. The main objective of the research is to demonstrate how freelancing can provide income generation, skill development, social support, and economic stability for youth.A qualitative methodology was employed, with data collected from various sources including books, reports, interviews, and global case studies. The freelancing experiences of Afghanistan, Bangladesh, the Philippines, and Kenya were specifically examined.The findings reveal that freelancing represents a flexible and sustainable source of income that allows young people to access international labor markets from their homes. This not only improves their economic conditions but also contributes to greater social stability. Freelancing programs in Afghanistan in 2023 showed that thousands of youth were rescued from the threat of unemployment and experienced a positive transformation in their lives.The study recommends expanding professional training programs, establishing incubators, improving internet connectivity and equipment access, and fostering collaboration between public and private sectors. These measures can significantly reduce youth migration through freelancing opportunities and pave the way for broader economic development.
Keywords: Freelancing; Youth; Employment Opportunities; Economic Stability; Migration